1964
DOI: 10.3181/00379727-117-29700
|View full text |Cite
|
Sign up to set email alerts
|

Sites of Action of Growth Hormone in Cartilage

Abstract: Since the isolation of growth hormone many of its actions on the total organism have been widely investigated and well recognized. The present report describes an attempt to locate the cells, within the cartilage of the upper tibial epiphysis, which respond to the stimulus of growth hormone. With the aid of tritiated thymidine (both in vitro and in vivo), colchicine and the electron micro-6. Trowell, C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1966
1966
1992
1992

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The possibility should be borne in mind that the traditional assay for growth hormone, based on the increase in size of the epiphyseal cartilage, may depend in a similar way on the ability of the hormone to support differentiation of chondrocyte precursors. The inability of cultivated skeletal fragments to respond to growth hormone (29,31) is probably due to technical factors in the culture system and not, as had been believed previously, to an exclusively indirect mode of action of the hormone (17).…”
Section: Discussionmentioning
confidence: 96%
“…The possibility should be borne in mind that the traditional assay for growth hormone, based on the increase in size of the epiphyseal cartilage, may depend in a similar way on the ability of the hormone to support differentiation of chondrocyte precursors. The inability of cultivated skeletal fragments to respond to growth hormone (29,31) is probably due to technical factors in the culture system and not, as had been believed previously, to an exclusively indirect mode of action of the hormone (17).…”
Section: Discussionmentioning
confidence: 96%
“…The possibility that GH might regulate the rate of differentiation of prechondrocytes has only recently been recognized (32). Interestingly, more than 20 yr ago it was indeed suggested that GH stimulates longitudinal bone growth by stimulating cells in the germinal zone of the growth plate (28).…”
Section: Organization and Cell Kinetics Of The Epiphyseal Growthmentioning
confidence: 99%
“…At this stage of development endochondral ossification occurs in both proximal and distal directions. Gradually, a laminar organization of chondrocytes in the plate with progessively more mature cells develops in the distal direction (26)(27)(28). After the development of the epiphyseal center of ossification, the epiphyseal growth plate is constrained between two calcified surfaces.…”
Section: Organization and Cell Kinetics Of The Epiphyseal Growthmentioning
confidence: 99%
“…This IGF-I then interacts with chondrocytes, inducing proliferation by autocrine or paracrine mechanisms [Isaksson et al. 1987], The second hypothesis maintains that GH stimulates the local produc tion of IGF-I [Underwood etal.. 1986], Rigal [ 1964] demonstrated that chondrocytes of the ger minal zone are the targets of GH in the epiphysial growth plate. When GH and tritiated thymidine were injected into rabbits.…”
Section: Discussionmentioning
confidence: 99%